Intensity-modulated radiation therapy using TomoDirect for postoperative radiation of left-sided breast cancer including lymph node area: comparison with TomoHelical and three-dimensional conformal radiation therapy. (31st July 2019) - Takano, Shoko; Omura, Motoko; Suzuki, Ryoko; Tayama, Yumiko; Matsui, Kengo; Hashimoto, Harumitsu; Hongo, Hideyuki; Nagata, Hironori; Tanaka, Kumiko; Hata, Masaharu; Inoue, Tomio
Abstract: Intensity-modulated radiation therapy (IMRT) delivers an excellent dose distribution compared with conventional three-dimensional conformal radiation therapy (3D-CRT) for postoperative radiation including the lymph nodes in breast cancer patients. The TomoTherapy system, developed exclusively for IMRT, has two treatment modes: TomoDirect (TD) with a fixed gantry angle for beam delivery, and TomoHelical (TH) with rotational beam delivery. We compared the characteristics of TD with TH and 3D-CRT plans in the breast cancer patients. Ten consecutive women with left breast cancer received postoperative radiation therapy using TD including the chest wall/residual breast tissue and level II–III axial and supraclavicular lymph node area. Fifty percent of the planning target volume (PTV) was covered with at least 50 Gy in 25 fractions. TD, TH and 3D-CRT plans were created for each patient, with the same dosimetric constraints. TD and TH showed better dose distribution to the PTV than 3D-CRT. TD and 3D-CRT markedly suppressed low-dose spread to the lung compared with TH. Total lung V5 and V10 were significantly lower, while V20 was significantly higher in the TD and 3D-CRT plans. The mean total lung, heart and contralateral breast doses were significantly lower using TD compared with the other plans. Compared with 3D-CRT and TH, TD can provide better target dose distribution with optimal normal-organ sparing for postoperative radiation therapy including the chest wall/residual breast tissue and lymph node area in breast cancer patients. TD is thus a useful treatment modality in these patients.